Integration of New Sol-Gel Films Into Optical Chemical Sensors. (2016) - Scolan, E.; Smajda, R.; Weder, G.; Voirin, G.; Pugin, R.; Michou, Y.; Merienne, M.C.; Lyonnet, M.; Winzer, A.
Abstract: CSEM has developed new sol-gel based sensitive layers enabling the optical detection of volatiles and dissolved analytes with enhanced performances. These sol-gel films exhibit a hierarchical nanoporous structure. Dedicated optical readers have been developed to interrogate the optical signal of the sensitive sol-gel patches. Applications of this technology, focusing yet on O2, CO2, and pH detection, are illustrated with practical cases in aeronautics and environmental, health, and process monitoring.